Real-time multiple cross displacement amplification assay for rapid and sensitive detection of Haemophilus influenzae - Sun, Chunrong; Jia, Nan; Huang, Xiaolan; Xiao, Fei; Zhou, Juan; Zhang, Yu; Fu, Jin; Xu, Zheng; Qu, Dong; Cui, Xiaodai; Wang, Yi (Frontiers in Cellular and Infection Microbiology, 2022)
Haemophilus influenzae is an opportunistic pathogen usually causing bacteremia, meningitis, and pneumonia in children. Here, we developed a method based on multiple cross displacement amplification (MCDA) method and real-tme fluorescence technique for rapid detection of H. influenzae. A set of 10 primers was designed for the H. influenzae real-time MCDA reaction, and a core primer was modified with a restriction endonuclease recognition sequence, a fluorescent, and a quencher according to the principle of the real-time MCDA assay. The H. influenzae real-time MCDA reactions were performed using a fluorescence instrument at 63°C for 40 min. The H. influenzae real-time MCDA assay can specifically detect H. influenzae without any cross-reaction with other bacteria as our results confirmed. The sensitivity of our assay is as low as 10 CFU per reaction. To validate its feasibility, our assay was applied to 40 DNA extracted from sputum samples. The results obtained from H. influenzae real-time MCDA were compared with that of H. influenzae–loop-mediated isothermal amplification (H. influenzae-LAMP) and MCDA-based lateral flow biosensor (MCDA-LFB). The positive rate of the real-time MCDA assay was 62.5%, which was consistent with the H. influenzae-MCDA-LFB assay, but was more sensitive than H. influenzae-LAMP (57.5%). Furthermore, the H. influenzae real-time MCDA assay takes only 40 min, which was less than that of a traditional PCR test. Taken together, the H. influenzae real-time MCDA assay reported here offers a new and valuable diagnostic tool for the reliable and rapid detection of H. influenzae.